Pyrimidine metabolism regulator-mediated molecular subtypes display tumor microenvironmental hallmarks and assist precision treatment in bladder cancer - Wu, Zixuan; Li, Xiaohuan; Gu, Zhenchang; Xia, Xinhua; Yang, Jing (Frontiers in Oncology, 2023)
Background: Bladder cancer (BLCA) is a common urinary system malignancy with a significant morbidity and death rate worldwide. Non-muscle invasive BLCA accounts for over 75% of all instances of BLCA. The imbalance of tumor metabolic pathways is associated to tumor formation and proliferation. Pyrimidine metabolism (PyM) is a complicated enzymatic network that combines nucleoside salvage, de novo nucleotide synthesis, and catalytic pyrimidine degradation. Metabolic reprogramming has been linked to clinical prognosis in several types of cancer. However, it is unknown what role Pyrimidine metabolism Genes (PyMGs) play in the BLCA-fighting process. Methods: Predictive PyMGs were quantified in BLCA samples from the TCGA and GEO datasets. TCGA and GEO provided information on stemness indices (mRNAsi), gene mutations, copy number variations (CNV), tumor mutation burden (TMB), and accompanying clinical features. The prediction model was built using Lasso regression. Co-expression analysis was used to investigate the relationship between gene expression and purine metabolism. Results: PyMGs were found to be overexpressed in the high-risk sample in the absence of other clinical symptoms, showing that they have the capacity to predict BLCA outcome. In the high-risk group, GSEA revealed immunological and tumor-related pathways. Immune function and m6a gene expression were substantially different between the low- and high-risk groups. In BLCA patients, DSG1, C6orf15, SOST, SPRR2A, SERPINB7, MYBPH, and KRT1 may be connected to the oncology process. Immunological function and m6a gene expression differed significantly between the two groups. The prognostic model, CNVs, single nucleotide polymorphism (SNP), and drug sensitivity all showed substantial gene connection. Conclusions: The objective of this research is to identify and verify BLCA-associated PyMGs that may be used to guide prognosis and the immunological environment, as well as to offer evidence for the development of purine metabolism-related molecularly targeted therapeutics. As a result, PyMGs and their interactions with immune cells in BLCA may be therapeutic targets.